COOPERATION AND INTEGRATION IN THE REGION - Valerievich Nikitin, Alexander; Antsiferova, O.Yu. (Revista Gênero e Interdisciplinaridade, 2020)
The study aims at substantiating the convergence of the cooperation and integration principles when transforming the social division of labor, and, based on this, grounding the strategic parameters for developing sectors of the agro-industrial complex (AIC) in the region. In accordance with it, the necessity of developing a strategy that takes into account the inertial, local innovation and systemic innovative development scenarios has been substantiated. The features of each scenario related to improving the production as well meeting regional needs in these products have been determined. Forecast scenarios on developing agricultural sectors have been analyzed. According to this analysis, the potential formed in the Tambov Region is sufficient for implementing the innovative approach to solving technological problems on improving the production efficiency.